A Study on English transitive verbs in comparision with Vietnamese ones / Bùi Văn Tuấn; NHDKH Dr Dang Ngoc Huong - Bùi, Văn Tuấn
This paper attempts to examine the comparison between English and Vietnamese transitive verbs, and based on that, to offer some tentative suggestion for both English teachers and learners to overcome the challenges which may be encountered when learning English transitive verbs. Accordingly, a literature review on the related theories to the categories of transitive verbs was given, which aims to address the syntactic and semantic features of English transitive verbs. In addition to this, the author also identified the syntactic and semantic similarities and differences between English transitive verbs and their equivalents in Vietnamese. Besides, a survey was also carried out to collect the quantitative data among the respondents in Ha Dong Medical College by means of questionnaires, including one exercise which include 15 multiple-choice questions, designed as an English test to check the respondents’ knowledge on the usages of English transitive verbs. The result survey revealed that a majority of the participants have confused of the difference between transitive and intransitive verb, some of them mistook on distinguishing prepositions and adverbs, the exceptions with some verbs such as make, let... In views of these problems and limitations, the dissertation also reinforces the significances of the roles of both the learners and teachers to enhance the learning and teaching English transitive verbs. For English learners, it is recommended that they should be aware of the direct object and prepositional object, as well as avoid word-for-word translation. For teachers, they should focus on teaching the distinguishing transitive verbs and intransitive verbs, using real objects and actions, expanding online interactive activities and improving their translation skills.